Asymmetric impact of transportation on carbon emissions influencing SDGs of climate change. (May 2023) - Avotra, Andrianarivo Andriandafiarisoa Ralison Ny; Nawaz, Ahsan
Abstract: Transportation facilities have expanded globally because of rapid industrialization and economic growth. Transportation involves substantial use of energy therefore strongly linked with environmental pollution. This study intends to explore linkages among transport from air mode, combustible renewable energy and waste, GDP, energy use, oil prices, trade expansion, and carbon releases from airline transport. The data covered in the study ranged from 1971 to 2021. For the empirical analysis, the non-linear autoregressive distributed lag (NARDL) methodology has been applied in order to explore the asymmetric impact of the variables of interest. Prior to this, the augmented Dickey-Fuller (ADF) unit root test is applied whose results demonstrate that variables included in the model contain mixed order of integration. The NARDL estimates show that the "positive shock to air transport and positive and negative shock to energy usage results in the increase of CO2 emissions per capita in the long run. While, a "positive (negative) shock" to renewable energy use and trade expansion reduces (increases) transport-related carbon discharge. The Error Correction Term (ECT) carries a negative sign implying a stability adjustment in the long run. These asymmetric components in our study can be employed in cost-benefit analysis and encompass the environmental repercussions (asymmetric) of government and management actions. The study suggests that the government of Pakistan should promote financing for renewable energy consumption and clean trade expansion to achieve the sustainable development goals (SDGs) objective 13. Graphical abstract: Image 1 Highlights: Transportation involves substantial use of energy therefore strongly linked with environmental pollution. Exploring the linkages among transport from air mode, combustible renewable energy and waste, GDP, energy use, oil prices, trade expansion, and carbon releases Application of NARDL as asymmetric impact of transportation on carbon emission influencing SDGs-13. Providing a pathway for renewable energy consumption and clean trade expansion to achieve the SDGs-Climate change.